Characterizing steroid hormone receptor chromatin binding landscapes in male and female breast cancer - Severson, Tesa M.; Kim, Yongsoo; Joosten, Stacey E. P.; Schuurman, Karianne; van der Groep, Petra; Moelans, Cathy B.; ter Hoeve, Natalie D.; Manson, Quirine F.; Martens, John W.; van Deurzen, Carolien H. M.; Barbe, Ellis; Hedenfalk, Ingrid; et al. (Nature communications, 2018)
Male breast cancer (MBC) is rare and poorly characterized. Like the female counterpart, most MBCs are hormonally driven, but relapse after hormonal treatment is also noted. The pan-hormonal action of steroid hormonal receptors, including estrogen receptor alpha (ERα), androgen receptor (AR), progesterone receptor (PR), and glucocorticoid receptor (GR) in this understudied tumor type remains wholly unexamined. This study reveals genomic cross-talk of steroid hormone receptor action and interplay in human tumors, here in the context of MBC, in relation to the female disease and patient outcome. Here we report the characterization of human breast tumors of both genders for cistromic make-up of hormonal regulation in human tumors, revealing genome-wide chromatin binding landscapes of ERα, AR, PR, GR, FOXA1, and GATA3 and enhancer-enriched histone mark H3K4me1. We integrate these data with transcriptomics to reveal gender-selective and genomic location-specific hormone receptor actions, which associate with survival in MBC patients. Male breast cancer (MBC) is rare and largely hormonally driven. Here, the authors examine the action of steroid hormone receptors in male and female breast cancers and find gender selective hormone receptor action that associates with the survival of MBC patients.